Augmented Reality in Error Troubleshooting Inside Flexible Manufacturing Cells - Csokmai, Lehel; Tarca, Radu; Ovidiu, Moldovan (Recent Innovations in Mechatronics, 2015)
A new type of software framework for error troubleshooting in flexible manufacturing systems using a frame marker device. Our framework system meant to resolve the failures originated from the human-machine interface and to generate self-training from previous experience.